An indirect technique for assuring simplicity and marginal integrity of provisional restorations during full mouth rehabilitation - Youssef S. Al Jabbari; Abdulaziz Al-Rasheed; Jesse W. Smith; Anthony M. Iacopino (Elsevier, 2013)
Full mouth rehabilitation with fixed prosthodontics can be a time- and labor-intensive process. The use of provisional restorations allows the treating clinician to determine the functional and esthetic requirements of the definitive prostheses. However, in the case of full mouth rehabilitation, the individual preparation of provisional restorations for multiple teeth may complicate the provisional phase and increase the treatment time. This article describes a method to simplify the indirect fabrication of provisional restorations for full mouth reconstruction. Provisional restorations may be easily achieved by splinting the provisional restorations in sextants, trimming them according to red pencil marks around the prepared margins as guidelines, and fitting them in the laboratory, utilizing a second set of solid casts for the prepared teeth. Keywords: Fabrication of provisional, Fixed prosthodontics, Indirect technique, Provisional restorations, Full mouth rehabilitation